ANALISIS YURIDIS PEMBATALAN PERJANJIAN KERJASAMA SECARA SEPIHAK SEBAGAI PERBUATAN MELAWAN HUKUM (Studi Kasus Putusan Pengadilan Negeri Padangsidimpuan No. 24/Pdt.G/PN. Psp) - Naswardi Sihaloho (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Regarding to the cancellation of the agreement, in civil law, it is regulated about the cancellation of an agreement, as stated in Article 1266 of the Civil Code that the condition for an agreement to be canceled by one party is that the agreement must be reciprocal, there is a default, and the cancellation must be requested to the judge. If the cancellation which is made does not meet the conditions stipulated in Article 1226 of the Civil Code, then the agreement can be said to have conflicted with the legal principles and provisions stipulated in the Civil Code.As for the conclusion, the decision of Padangsidimpuan District Court No. 24/Pdt.G/2014/PN.Psp, the elements of unlawful acts have been fulfilled relatively, it's just that the losses that occurred in this case did not mention any immaterial losses. The act against the law in this case has not yet fully occurred. The legal consequences of unilaterally canceling an agreement that are not based on a clear reason can be sued as an act against the law or a breach of contract. In the case of a lawsuit based on tort, it will lead to legal consequences in the form of replacing any losses arising from such actions. If the lawsuit is based on a default, then the party who is canceling the agreement can be sued for material losses due to the cancellation of the agreement. The consideration of the Padangsidimpuan District Court in dropping a lawsuit for unilaterally canceling the agreement is that the cancellation made by the defendant was not based on clear reasons justified by law as stipulated in Article 1266 of the Civil Code. Keywords: Cancellation of Agreement, Action against the law .